Improving testing capacity for COVID-19: experiences and lessons from Senegal, Uganda, Nigeria, and the Democratic Republic of Congo - Bosonkie, Marc; Egbende, Landry; Namale, Alice; Fawole, Olufunmilayo I.; Seck, Ibrahima; Kizito, Susan; Kaba, Didine; Kiwanuka, Suzanne N.; Diallo, Issakha; Bello, Segun; Kabwama, Steven N.; Kashiya, Yves; et al. (Frontiers in Public Health, 2023)
Background: African countries leveraged testing capacities to enhance public health action in response to the COVID-19 pandemic. This paper describes experiences and lessons learned during the improvement of testing capacity throughout the COVID-19 response in Senegal, Uganda, Nigeria and the Democratic Republic of the Congo (DRC). Methods: The four countries’ testing strategies were studied using a mixed-methods approach. Desk research on COVID-19 testing strategies was conducted and complemented by interviewing key informants. The findings were synthesized to demonstrate learning outcomes across the four countries. Results: The four countries demonstrated severely limited testing capacities at the onset of the pandemic. These countries decentralized COVID-19 testing services by leveraging preexisting laboratory systems such as polymerase chain reaction (PCR) and GeneXpert used for the diagnosis of tuberculosis (TB) to address this gap and the related inequities, engaging the private sector, establishing new laboratories, and using rapid diagnostic tests (RDTs) to expand testing capacity and reduce the turnaround time (TAT). The use of digital platforms improved the TAT. Testing supplies were sourced through partners, although access to global markets was challenging. Case detection remains suboptimal due to high costs, restrictive testing strategies, testing access challenges, and misinformation, which hinder the demand for testing. The TAT for PCR remained a challenge, while RDT use was underreported, although Senegal manufactured RDTs locally. Key findings indicate that regionally coordinated procurement and manufacturing mechanisms are required, that testing modalities must be simplified for improved access, and that the risk-based testing strategy limits comprehensive understanding of the disease burden. Conclusions: Although testing capacities improved significantly during the pandemic, case detection and access to testing remained suboptimal. The four countries could benefit from further simplification of testing modalities and cost reduction. Local manufacturing and pooled procurement mechanisms for diagnostics are needed for optimal pandemic preparedness and response.